2018
DOI: 10.1017/s0033291718001630
|View full text |Cite
|
Sign up to set email alerts
|

Access to awareness of direct gaze is related to autistic traits

Abstract: These results provide the first evidence that differences in gaze processing and the sensitivity to direct gaze are already present in individuals with subclinical levels of autistic traits. Furthermore, they lend support to the continuum view of the disorder and could potentially help in an earlier diagnosis of individuals at high risk for autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(65 reference statements)
3
13
0
Order By: Relevance
“…In line with previous studies [ 39 42 , 88 ], our neurotypical participants displayed a marked preference for direct gaze. By contrast, no preference, either for direct or averted gaze, emerged in our autistic participants, in line with previous studies [ 42 , 88 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies [ 39 42 , 88 ], our neurotypical participants displayed a marked preference for direct gaze. By contrast, no preference, either for direct or averted gaze, emerged in our autistic participants, in line with previous studies [ 42 , 88 ].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies [ 39 42 , 88 ], our neurotypical participants displayed a marked preference for direct gaze. By contrast, no preference, either for direct or averted gaze, emerged in our autistic participants, in line with previous studies [ 42 , 88 ]. Whereas some authors have suggested that autistic individuals have trouble identifying subtly averted gaze [ 37 , 38 ], in our study, the manipulation between subtle and obvious averted gaze seemed to influence neither the neurotypical participants’ preference for direct gaze nor the absence of any preference in autistic participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Its disruption can lead to social dysfunction, evidenced by reports of abnormal eye contact perception in conditions often accompanied by social deficits, including autism-spectrum disorder (ASD) [5], social anxiety [6][7][8], schizophrenia [9][10][11], and bipolar disorder [12]. A relation between gaze processing and the strength of autism, social anxiety, schizotypal traits has also been found in subclinical populations [13][14][15]. These findings suggest that gaze perception is a functional dimension cutting across categories of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Inter-individual variability in breakthrough time depends on individual factors related to the stimuli that compete for perceptual dominance. For example, the advantage for faces with direct gaze in gaining access to awareness is reduced in individuals with autistic traits (Madipakkam et al, 2018). Similarly, suppression times are reduced for sad faces in patients with major depression (Sterzer et al, 2011) and for spider stimuli in individuals with spider phobia (Schmack et al, 2016).…”
Section: Introductionmentioning
confidence: 99%